First Record of Cnestus mutilatus (Coleoptera, Curculi-onidae) in Croatia - Andrija Jukić; Filip Cvetković; Tomislav Krcivoj; Jasnica Medak; Nikola Zorić; Nevenka Ćelepirović; Dinka Matošević (South-East European Forestry)
Non-native ambrosia beetles (Coleoptera; Curculionidae; Scolytinae) have been recognized as pests in introduced areas that can significantly influence tree and forest health. Cnestus mutilatus (Coleoptera, Curculionidae) is native to Asia and is polyphagous, attacking wide range of deciduous forest trees. Our research has found C. mutilatus in traps and on branches in a forest stand in Pleternica in Croatia on Fagus sylvatica, Quercus rubra and Carpinus betulus in 2024 and 2025. Exit holes, adult galleries and the presence of adult beetles were recorded on branches with diameters ranging from 10 to 25 mm. Adults were also caught in traps baited with a pheromone lure for Agrilus spp. This is the first record of C. mutilatus in Croatia. Raised population levels of C. mutilatus could negatively influence young plants used in forest regeneration. Monitoring will be continued in the affected area, with enhanced data collection through the deployment of pheromone traps in the canopy.